2021
DOI: 10.3724/sp.j.1042.2021.01313
|View full text |Cite
|
Sign up to set email alerts
|

I am gifted! Perceived overqualification and its influence on employees

Abstract: Over-qualification and the dimensions of job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…When employees feel overqualified, their skills, knowledge and experience are not fully utilized, which is not only a waste of resources, but also hinders the process of accumulating more resources. Therefore, employees will feel the loss of their resources (Li et al, 2021a , b ; Wei et al, 2020 ) proposed that once people realize the possibility of resource loss, they will try to avoid it. Therefore, when employees perceive overqualification, they will reduce affective and cognitive engagement, and may be reluctant to devote extra time and energy to produce radical creativity.…”
Section: Theory and Hypothesementioning
confidence: 99%
See 1 more Smart Citation
“…When employees feel overqualified, their skills, knowledge and experience are not fully utilized, which is not only a waste of resources, but also hinders the process of accumulating more resources. Therefore, employees will feel the loss of their resources (Li et al, 2021a , b ; Wei et al, 2020 ) proposed that once people realize the possibility of resource loss, they will try to avoid it. Therefore, when employees perceive overqualification, they will reduce affective and cognitive engagement, and may be reluctant to devote extra time and energy to produce radical creativity.…”
Section: Theory and Hypothesementioning
confidence: 99%
“…Therefore, researchers’ focus in current study was perceived overqualification. Perceived overqualification will bring a series of negative effects, Li, Wen et al ( 2021 ); Li, Chen et al ( 2021 ) carried out a meta-analysis which showed that it would reduce employees’ positive perception of the organization, work and themselves, resulting in negative work attitude (e.g., low job involvement) and work behavior (e.g., counterproductive behavior), as well as low work performance (e.g., task performance), and can damage their physical and mental health (e.g., pressure and depressive symptoms). However, some scholars have pointed out that perceived overqualification may also lead to some positive effects, depending on how employees view their employment status.…”
Section: Introductionmentioning
confidence: 99%
“…And employees may feel that they're not performing as well as they should (Huang and Peng, 2017 ; Yuan et al, 2018 ). As a result, employees' self-esteem and core self-evaluation of the organization will be reduced, which will lead them to re-evaluate their own resources and recognize the gap between reality and ideal (Li et al, 2021 ). At the same time, Self-regulation Theory (SR) (Bandura et al, 1980 ) points out that individuals can achieve personal goals by adjusting self-cognition, emotion, and other behaviors and narrowing the gap between reality and ideal according to the gap between reality and ideal.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Based on self-representation theory, they found that perceived overqualification would lead to negative emotions such as frustration, anger and hostility, thus reduce organizational self-esteem and bring psychological pressure to employees. COR holds that the sense of resource loss of overqualified employees will lead to negative physical and mental outcomes, work attitudes and behaviors ( Wassermann and Hoppe, 2019 ; Li et al, 2021 ). Therefore, grounding on the COR, this study takes the view that the frustration caused by underutilization of qualification to explore perceived overqualification, specifically, in the employment situation where the qualifications are not fully utilized.…”
Section: Theory and Hypothesementioning
confidence: 99%